Modeling and analysis of doubly fed induction generator wind energy systems - Fan, Lingling, 1973- (Academic Press, 2015)
This book provides key information on machine/converter modelling strategies based on space vectors, complex vector, and further frequency-domain variables. It includes applications that focus on wind energy grid integration, with analysis and control explanations with examples and looks at how wind energy is modelled, what kind of control systems are adopted, how it interacts with the grid, as well as suitable study approaches. Principles behind the dynamics of wind energy grid integration system, different strategies for analysis, such as frequency-domain-based and state-space-based approaches are described. The resource focuses on real and reactive power control; is supported by PSCAD and Matlab/Simulink examples; considers the difference in control objectives between ac drive systems and grid integration systems. --